Novel Coronavirus disease 2019 (COVID-19): The importance of recognising possible early ocular manifestation and using protective eyewear - Li, Ji-Peng Olivia; Lam, Dennis Shun Chiu; Chen, Youxin; Ting, Daniel Shu Wei (British journal of ophthalmology, 2020)
SARS emerged in 2003 and caused the first pandemic of the 21st century, affecting more than 8000 people, killing 774 in 26 countries.5 MERS coronavirus (MERS-CoV) was isolated in 20126 and has seen over 2400 cases reported to WHO to date, and over 850 deaths.7 Of the 2223 laboratory-confirmed MERS-CoV cases reported to WHO, 415 were healthcare workers, representing over one-third of all secondary transmission.8 SARS and MERS spread principally by direct transmission and respiratory droplets.9 10 However, SARS-CoV, and perhaps also MERS-CoV, may shed and be transferred to environmental surfaces, and thence contaminate hands and mucous membranes subsequently.10 Ocular involvement has not been described with either MERS-CoV or SARS-CoV11–13 although polymerase chain reaction on tears from patients with SARS-CoV infection demonstrated presence of the virus.14 There is also evidence that some coronavirus can occasionally cause conjunctivitis in humans. [...]human coronavirus NL 63 (HCoV-NL63) was first identified in a baby with bronchiolitis and conjunctivitis.15 Subsequent in 28 cases of children with confirmed HCoV-NL63 infections, 17% had conjunctivitis.16 There is now growing evidence that human-to-human transmission is occurring among close contacts, and reports that >1,700 healthcare professionals having been infected with 6 deaths including oneophthalmologist.17–19 Of the affected healthcare workers, one was part of the expert task force who visited Wuhan, and he has reflected on his experience of the disease. The usual measures that apply to prevention of infection transmission, in particular thorough handwashing, should apply. [...]we learn more, it is prudent to avoid touching the eyes where possible in at risk locations, in particular for healthcare workers in the hospital environment. Healthcare professionals should take the full recommended measures including strict hand hygiene and protecting the exposed mucous membranes, including wearing goggles or face masks.25 It would be prudent to question patients directly if they had any symptoms and signs of conjunctivitis prior respiratory and other systemic symptoms to help further our understanding of the natural history of the disease.